2019
DOI: 10.1037/edu0000331
|View full text |Cite
|
Sign up to set email alerts
|

Motivation in transition: Development and roles of expectancy, task values, and costs in early college engineering.

Abstract: This longitudinal study investigated development in expectancy for success (perceived competence), 3 types of task value (utility, interest, attainment), and 3 types of perceived cost (opportunity, effort, psychological) for engineering students during their first 2 years of college. Latent growth curve models indicated declines in expectancy and values, with attainment value declining more slowly than expectancy, interest value, and utility value. Costs increased over time, with effort cost increasing more ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
131
3
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 134 publications
(162 citation statements)
references
References 87 publications
(235 reference statements)
26
131
3
2
Order By: Relevance
“…While prior research has indicated that identity-related beliefs may decline on average in the long- and short-term, suggesting broad-based supports are needed to buffer students’ motivational trajectories, we investigated heterogeneous semester-long trajectories of science identity in an effort to capture the nature and prevalence of typical development in a large introductory course. Building on prior research examining long-term trajectories (Robinson, Perez, et al (2018); Robinson, Lee, et al, 2018), our findings inform the theoretical conceptualization of attainment value as largely stable, though with the potential for rapid change even within a single semester. Indeed, though identity-related beliefs are often conceptualized as relatively stable, our results indicate that some students in a gateway chemistry course experienced sharp declines in science identity within a single semester.…”
Section: Resultssupporting
confidence: 63%
See 3 more Smart Citations
“…While prior research has indicated that identity-related beliefs may decline on average in the long- and short-term, suggesting broad-based supports are needed to buffer students’ motivational trajectories, we investigated heterogeneous semester-long trajectories of science identity in an effort to capture the nature and prevalence of typical development in a large introductory course. Building on prior research examining long-term trajectories (Robinson, Perez, et al (2018); Robinson, Lee, et al, 2018), our findings inform the theoretical conceptualization of attainment value as largely stable, though with the potential for rapid change even within a single semester. Indeed, though identity-related beliefs are often conceptualized as relatively stable, our results indicate that some students in a gateway chemistry course experienced sharp declines in science identity within a single semester.…”
Section: Resultssupporting
confidence: 63%
“…One study examining engineering identity alongside expectancy, other task values, and perceived costs found average declines throughout the first two years of college, but identity declined at a slower rate than expectancy and other task values (Robinson, Lee, et al, 2018). Jacobs and colleagues (2002) documented declines in math-related task value (a composite of interest, utility, and broad importance) from first through twelfth grade.…”
Section: Development Of Science Identity During Collegementioning
confidence: 99%
See 2 more Smart Citations
“…area (Gaspard et al, 2018;Hagemeier & Murawski, 2014;Lauermann, Tsai, & Eccles, 2017;Perez, Cromley, & Kaplan, 2014;Perez et al, 2019;Robinson et al, 2019;Simons, Dewitte, & Lens, 2003;Tulis & Fulmer, 2013;Wang, Degol, & Ye, 2015;Wu & Fan, 2017).…”
Section: Subjective Value In Academic Goal Pursuitmentioning
confidence: 99%